HUBUNGAN STATUS EKONOMI DAN KONDISI FISIK LINGKUNGAN RUMAH DENGAN KEJADIAN TB PARU - Karlina, Nonok; Aris, Muhammad; Sendra, Eny; Jenice Sanaky, Marisca; Yulia, Mega (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Tuberkulosis (TB) is an infectious disease which is caused by tuberculosis mycobacterium bactery which can attack some various organs, especially the lungs. Based on data of Pekanbaru health office in 2017. The rejosari healthy center in Pekanbaru city was the healthy center which ranked the first of tuberculosis case, and also the highest numberof pulmonary TB cases at 155 cases. The result of the initial survey research around the working area of Rejosary healthy center in Pekanbaru city, the physical condition of society’s home environments in the working area of Rejosari Public healthy center in Pekanbaru City were mostly inadequate, where the researcher saw that moost of the houses had buildings which had not been permanent and the distance between each house was close enough. The purpose of this research was to determine the reletionship of economic status and physical condition of the reletionship of economic status and physical condition of the society’s home environment with the incident of pulmonary TB disease in the rejosari areal healthy center in Pekanbaru. The method of this research is quantitative researching with a sectional cross design. The samples which were taken by researching with a sectional cross design. The samples which were taken by the researcher was a random sampling by taking samples from the society population based on certain criteria The sample which was as many as 78 respondents. The data collection tool is a questionnaire. Data analysis was done by univariate by using the chis square test with a limit of 95% significance level. The results founded that there was a significant relationship between economic status (p value 0,001) and home environments which includes ventilation (p value 0,011), lighting (p value 0,007), wall (p value 0,011), occupancy (p value 0,026), and humidity (p value 0,007).Keywords: Tuberculosi, economic status, physical condition of the home environment